2020
DOI: 10.1093/tbm/ibz198
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of physical activity and quality of life and well-being

Abstract: Maintaining or improving quality of life (QoL) and well-being is a universal goal across the lifespan. Being physically active has been suggested as one way to enhance QoL and well-being. In this systematic review, conducted in part for the 2018 U.S. Health and Human Services Physical Activity Guidelines for Americans Scientific Advisory Committee Report, we examined the relationship between physical activity (PA) and QoL and well-being experienced by the general population across the lifespan and by persons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
112
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(179 citation statements)
references
References 100 publications
9
112
0
5
Order By: Relevance
“…We observed that higher PA levels were associated with better QoL, in accordance with previous studies [ 3 5 ]. Although current study design does not allow a causal relationship to be concluded, existing evidence has shown that PA improves health related QoL [ 19 ]. Interestingly, for those who were physically active (GLTEQ score > 24, n = 16), PA levels did not correlate with QoL (Spearman’s correlation coefficient 0.21, p = 0.43), nor did it with lower fatigue levels (Spearman’s correlation coefficient 0.25, p = 0.35).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that higher PA levels were associated with better QoL, in accordance with previous studies [ 3 5 ]. Although current study design does not allow a causal relationship to be concluded, existing evidence has shown that PA improves health related QoL [ 19 ]. Interestingly, for those who were physically active (GLTEQ score > 24, n = 16), PA levels did not correlate with QoL (Spearman’s correlation coefficient 0.21, p = 0.43), nor did it with lower fatigue levels (Spearman’s correlation coefficient 0.25, p = 0.35).…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of physical activity on HRQL in older individuals are well known 17,18 . In this context, we hypothesized that home confinement due to COVID-19 pandemic would result in reduction of physical activity and, consequently, HRQL in participants of present.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of literature suggesting that regular practice of physical activity can improve individuals’ health, quality of life, physical and emotional well-being [ 1 , 2 ], reducing the incidence and the implications of many diseases and disabilities [ 3 6 ]. Despite this scientific evidence, globally, one out of four adults do not meet the global recommended levels of physical activity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%